A deeper look at long-term effects of COVID-19 on myocardial function in survivors with no prior heart diseases: a GRADE approach systematic review and meta-analysis - Dehghan, Mahshid; Mirzohreh, Seyedeh-Tarlan; Kaviani, Raheleh; Yousefi, Shiva; Pourmehran, Yasaman (Frontiers in Cardiovascular Medicine, 2024)
ObjectivesThe COVID-19 pandemic has challenged global health systems since December 2019, with the novel virus SARS-CoV-2 causing multi-systemic disease, including heart complications. While acute cardiac effects are well-known, long-term implications are understudied. This review hopes to fill a gap in the literature and provide valuable insights into the long-term cardiac consequences of the virus, which can inform future public health policies and clinical practices.MethodsThis systematic review was prepared using PRISMA reporting guidelines. The databases searched were PubMed, Scopus, Web of Science, and Cochrane. Risk of Bias was assessed using ROBINS-I. The GRADE approach was employed to evaluate the level of certainty in the evidence for each outcome. A meta-analysis was conducted using the Comprehensive Meta-Analysis (CMA) software. In order to identify the underlying cause of high heterogeneity, a subgroup analysis was conducted. Sensitivity analysis was checked.ResultsSixty-six studies were included in this review. Thirty-two of them enrolled in meta-analysis and the rest in qualitative synthesis. Most outcomes showed a moderate certainty of evidence according to the GRADE framework. Post-COVID individuals with no prior heart diseases showed significant changes in left ventricular (LV) and right ventricular (RV) echocardiographic indices compared to controls. These significant findings were seen in both post-acute and long-COVID survivors regardless of the severity of initial infection.ConclusionThis review implies that individuals recovering from post-acute and long-term effects of COVID-19 may experience changes in myocardial function as a result of the novel coronavirus. These changes, along with cardiac symptoms, have been observed in patients without prior heart diseases or comorbidities.Systematic Review RegistrationPROSPERO, identifier (CRD42024481337).